2021
DOI: 10.1002/chem.202103311
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination Reactions at a Platinum Carbene Complex: Reaction Routes to SF3, S(=O)F and Fluorido Complexes

Abstract: The electron‐rich Pt complex [Pt(IMes)2] (IMes: [1,3‐bis(2,4,6‐trimethylphenyl)‐2‐imidazolinylidine]) can be used as precursor for the syntheses of a variety of fluorido ligand containing compounds. The sulfur fluoride SF4 undergoes a rapid oxidative addition at Pt0 to yield trans‐[Pt(F)(SF3)(IMes)2]. A photolytic reaction of SF6 at [Pt(IMes)2] in the presence of IMes gave the fluorido complexes trans‐[Pt(F)2(IMes)2] and trans‐[Pt(F)(SF3)(IMes)2] along with trans‐[Pt(F)(SOF)(IMes)2] and trans‐[Pt(F)(IMes’)(IMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 148 publications
1
5
0
Order By: Relevance
“…The 19 F NMR spectra of 3 a‐f revealed a triplet of triplets with 195 Pt satellites for the fluorido ligands due to coupling with the N H protons and the two phosphorus nuclei (Figure 2, top). The observed chemical shifts between δ =‐267.7 ppm – ‐280.0 ppm and the 2 J (F,P) coupling constants of 13–14 Hz are typical values for Pt fluorido complexes bearing phosphine ligands in a cis position [1e,p,4c,5a,c,f,h,j,k, 6–7,28] . The observed | 1 J (F,Pt)| coupling constants (567‐517 Hz) have comparable values to those reported for the fluorido complexes trans [‐Pt(F)(CH 3 ){R 2 P(Ind)} 2 ] (R=Ph, 4‐FC 6 H 4 , 4‐CF 3 C 6 H 4 ) [12] …”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The 19 F NMR spectra of 3 a‐f revealed a triplet of triplets with 195 Pt satellites for the fluorido ligands due to coupling with the N H protons and the two phosphorus nuclei (Figure 2, top). The observed chemical shifts between δ =‐267.7 ppm – ‐280.0 ppm and the 2 J (F,P) coupling constants of 13–14 Hz are typical values for Pt fluorido complexes bearing phosphine ligands in a cis position [1e,p,4c,5a,c,f,h,j,k, 6–7,28] . The observed | 1 J (F,Pt)| coupling constants (567‐517 Hz) have comparable values to those reported for the fluorido complexes trans [‐Pt(F)(CH 3 ){R 2 P(Ind)} 2 ] (R=Ph, 4‐FC 6 H 4 , 4‐CF 3 C 6 H 4 ) [12] …”
Section: Resultssupporting
confidence: 69%
“…The observed chemical shifts between δ =‐267.7 ppm – ‐280.0 ppm and the 2 J (F,P) coupling constants of 13–14 Hz are typical values for Pt fluorido complexes bearing phosphine ligands in a cis position. [ 1e , 1p , 4c , 5a , 5c , 5f , 5h , 5j , 5k , 6 , 7 , 28 ] The observed | 1 J (F,Pt)| coupling constants (567‐517 Hz) have comparable values to those reported for the fluorido complexes trans [‐Pt(F)(CH 3 ){R 2 P(Ind)} 2 ] (R=Ph, 4‐FC 6 H 4 , 4‐CF 3 C 6 H 4 ). [12] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactivity studies of SF 3 complexes showed that SF 3 ligands can be converted into S(O)F groups by hydrolysis or by deoxyfluorination in the presence of EtOH, whereas a fluoride abstraction occurs in the presence of strong Lewis acids like BF 3 or AsF 5 to form cationic SF 2 complexes [6] . A Pt S(O)F carbene complex has been synthesized by oxidative addition of SOF 2 at a Pt(0) center [6e] . In contrast, reactions of SO 2 F 2 (sulfuryl fluoride) or SO 2 FCl with various transition metal complexes so far led solely to the halogenation of the metal, but not to the stabilization of SO 2 F ligands [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting approach includes the synthesis of trans ‐[Pt(F)(SF 3 )(PCy 3 ) 2 ] either by reaction of [Pt(PCy 3 ) 2 ] with SF 4 or by activation of SF 6 . In reactivity studies the deoxyfluorination of ethanol and benzophenone was achieved [4e,f,k] …”
Section: Introductionmentioning
confidence: 99%